2018
DOI: 10.1177/0894845318786460
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Analysis of Early Career Women’s Adjustment to Work in Professional Psychology: Practitioners’ Reflections

Abstract: The experiences of early career psychologists (ECPs) have become a focal point within the profession of psychology, with trends reflecting increasing financial burdens and career struggles. Despite these trends, few attempts to directly explore themes among the experiences of ECP women’s career adjustment in clinical settings have been published. In this study, consensual qualitative research (CQR) methodology was used to extract themes among a sample of recently licensed ECPs ( N = 13) identifying as women in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Mentoring has received a great deal of research attention since Kram’s (1985) seminal work 35 years ago (e.g., Eby et al, 2013; Kammeyer-Mueller & Judge, 2008; Scalise et al, 2019; Turban et al, 2017; Wen et al, 2019). This substantial body of literature has typically focused on the positive outcomes of workplace mentoring for protégés and organizations and the mentor–protégé dyad.…”
mentioning
confidence: 99%
“…Mentoring has received a great deal of research attention since Kram’s (1985) seminal work 35 years ago (e.g., Eby et al, 2013; Kammeyer-Mueller & Judge, 2008; Scalise et al, 2019; Turban et al, 2017; Wen et al, 2019). This substantial body of literature has typically focused on the positive outcomes of workplace mentoring for protégés and organizations and the mentor–protégé dyad.…”
mentioning
confidence: 99%
“…The present study aimed to understand the role that PsyCap and employability played in the OCS of individuals working in OP. In doing so, we responded to calls for context-specific career research ( Scalise et al, 2019 ; Weng and Zhu, 2020 ) by focusing on a professional group of occupational psychology professionals, provided an important contribution to extant employability literature, also adopting the competence-based conceptualisation of employability ( Van der Heijde and Van der Heijden, 2006 ), not previously explored in a UK context, but relevant for our hypotheses. As predicted, in H1, we observed a positive relationship between PsyCap and employability, and despite predicting that we would observe a partial mediation between the study variables (H2), we found evidence to support a fully mediated model.…”
Section: Discussionmentioning
confidence: 99%
“…Some empirical work investigates employability amongst academic staff, hospital and care staff, and manufacturing staff in the Dutch workforce ( Van der Klink et al, 2014 ; Veth et al, 2015 ; Van der Heijden et al, 2016 ; Van der Heijden and Spurk, 2019 ); yet, research on working UK populations is scarce. In addition, we respond to calls to understand the context ( Scalise et al, 2019 ; Weng and Zhu, 2020 ), in career research by concentrating on a homogeneous sample of UK-based occupational psychology (OP) professionals, where “occupational expertise” defines career and leads, therefore, to the adoption of the competence-based model of employability ( Van der Heijde and Van der Heijden, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…As women enter the workforce, they are continually engaged in the negotiation between their personal lives and their lives at work (Hite & McDonald, 2003;Raskin et al, 1998;Whitmarsh et al, 2007). Women also endorsed career barriers within their specific careers, including difficulty in securing adequate mentoring experiences, sexual harassment, inadequate pay, difficulties with advancement, and pressure to compromise career for family (Brooks & Daniluk 1998;Darvin, 2020;Hite & McDonald, 2003;Moffitt, & Szymanski, 2011;O'Shaughnessy & Burnes, 2016;Reybold & Alamia, 2008;Richie et al, 1997;Scalise et al, 2019), which may have implications for realistic perceptions of one's own ability (Betsworth, 1999). These career barriers were often more strongly felt for women in nontraditional careers (Whiston et al, 2015;Whitmarsh et al, 2007) and women of Color (C. Brown et al, 2005;Moffit & Szymanski, 2011;Richard & Lee, 2019;Richie et al, 1997).…”
Section: Women In the Workforcementioning
confidence: 99%